АКТУАЛЬНІ ПИТАННЯ МОНІТОРИНГУ І ТЕХНІЧНОГО ОБСЛУГОВУВАННЯ ВИСОКОВОЛЬТНИХ ВИМИКАЧІВ - Панов, А.В.; Паньків, В.І.; Сопель, М.Ф.; Стогній, Б.С.; Танкевич , Є.М. (Інститут електродинаміки НАН України, Київ, 2018)
The factors that determine need to change the maintenance strategy for high-voltage circuit breaker were identified - the gradual transition from time-based service to service based on the evaluation of the technical condition of the circuit breaker and its reliability. It is shown that the most important condition for the introduction of advanced systems of technical maintenance and control of the technical condition of this highly responsible electrical equipment of power systems is the construction of its on-line monitoring systems. The urgent issues of such systems designing were identified and studied, among which the development, selection and scientific explanation of effective methods of signal processing and analysis of different kinds of sensors of information about the technical condition of circuit breaker is recognized as the most important. References 51, table 1.